Sistem Tapping Fasa Keseimbangan Beban Berbasis Internet of Things - Satria Utomo; Agus Adhi Nugroho; Muhammad Khosyi'in (Institut Teknologi Dirgantara Adisutjipto, 2022)
Load imbalance that occurs continuously will decrease in the reliability of a system, the maximum limit for load imbalance, according to IEEE Std 446-1995 is 20% in each phase. The design of a prototype for the management of 1-phase loading electrical energy using the Blynk platform as a user interfaces, monitor and controller. The phase shift method reduces the percentage value of the load imbalance in the electrical energy distribution system. An Energy Meter is used for measuring the electrical quantities and detecting unbalanced phases. Arduino Mega and ESP 8266-01 are used to communicate data as sending and receiving commands from Blynk, testing before balancing the measured load on the Energy Meter. The R phase has a current of 0.36 Ampere, The S phase is 0.71 Ampere, and 0.00 Ampere in the T phase. The percentage before load imbalance shows a value of 100%. After balancing the load, the measured current becomes 0.41 Ampere in the R phase, 0.44 Ampere in the S phase, and the 0.39 Ampere for T phase. The value of the load imbalance decreased to 17.7%.